Validation of Parkinson’s Disease-Related Questionnaires in South Africa - Gill Nelson; Ntombizodwa Ndlovu; Nicola Christofides; Tintswalo M. Hlungwani; Irene Faust; Brad A. Racette (Parkinson's Disease)
Background. There are very few epidemiological studies investigating Parkinson’s disease (PD) in Africa. The hundreds of local languages and dialects make traditional screening and clinical evaluation tools difficult to use. Objective. The objective of the study was to validate two commonly used PD questionnaires in an African population. Methods. The PD Screening Questionnaire (PDSQ) and Parkinson’s Disease Questionnaire (PDQ-39) were modified and translated into Afrikaans, Setswana, and isiZulu and administered to a sample of healthy local residents. We assessed the internal consistencies and cluster characteristics of the questionnaires, using a Cronbach’s alpha test and exploratory factor analysis. The questionnaires were then administered to a population-based sample of 416 research participants. We evaluated the correlations between the questionnaires and both a timed motor task and the Unified Parkinson’s Disease Rating Scale motor subsection 3 (UPDRS3), using locally weighted scatterplot smoothing (LOWESS) regression analysis and Spearman’s rank correlation. Results. Both questionnaires had high overall internal consistency (Cronbach’s alpha = 0.86 and 0.95, respectively). The modified PDQ-39 had evidence of five subscales, with Factor 1 explaining 57% and Factor 2 explaining 14%, of the variance in responses. The PDSQ and PDQ-39 scores were correlated with the UPDRS3 score (ρ = 0.35, P<0.001; and ρ = 0.28, P<0.001, respectively). Conclusion. The translated PDSQ and PDQ-39 questionnaires demonstrated high internal consistency and correlations with clinical severity of parkinsonism and a timed motor task, suggesting that they are valid tools for field-based epidemiological studies.